Peningkatan Pengetahuan Petugas Tracing (Tracer) dan Kinerja Program COVID-19 Kota Depok Mengenai Pelacakan Kontak (Contact Tracing) Tahun 2020 - Syaputri, Nadhiratul; Wahyono, Tri Yunis Miko; Wahyuningsih, Tri (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: COVID-19 cases in Depok City continued to increase until November 2020, so case tracking and close contact (tracing) are needed to suppress COVID-19 cases. However, tracing officers still face obstacles in conducting case tracking and close contact (tracing). The purpose of this study is to improve the knowledge of tracing officers and see the performance of the Depok City COVID-19 program in terms of contact tracing.Methods: The design of this study was One Group Pretest-Posttest, consisting of 121 participants using virtual lecture methods and online assignments through Zoom Meeting and Google Form. The collected data were analyzed with STATA.12 (paired t test) to see the difference in the mean scores of participants between pretest and posttest. In addition, SPSS.24 (paired t test and Wilcoxon) was also used to see the achievement of the COVID-19 search program.Results: The statistical test results showed that this training increased the knowledge of COVID-19 trackers in Depok City with a p-value <0.05. The average score before the training was 69.89 and after the training increased to 84.89.Conclusion: The successful implementation of case and contact finding is strongly influenced by the community and the number of officers needed to trace COVID-19 cases, and is supported by the availability of COVID-19 test kits at the examining laboratory.